On Bending of Piezoelectrically Layered Perforated Nanobeams Embedded in an Elastic Foundation with Flexoelectricity - Alaa A. Abdelrahman; Hussein A. Saleem; Gamal S. Abdelhaffez; Mohamed A. Eltaher (Mathematics, 2023)
Analysis of the electromechanical-size-dependent bending of piezoelectric composite structural components with flexoelectricity has been considered by many researchers because of the developments of nanotechnology and the applicability of piezoelectric composite nanobeam structures in Micro/Nano-Electro-Mechanical Systems (MEMS/NEMS). Therefore, the work investigates the size-dependent electromechanical bending of piezoelectrically layered perforated nanobeams resting on elastic foundations including the flexoelectric effect. Within the framework of the modified nonlocal strain gradient elasticity theory, both the microstructure and nonlocality effects are captured. The governing equilibrium equations including piezoelectric and flexoelectric effects are derived using Hamilton’s principle. Closed forms for the non-classical electromechanical bending profiles are derived. The accuracy of the proposed methodology is verified by comparing the obtained results with the available corresponding results in the literature within a 0.3% maximum deviation. Parametric studies are conducted to explore effects of perforation parameters, elastic foundation parameters, geometric dimensions, nonclassical parameters, flexoelectric parameters, as well as the piezoelectric parameters on the bending behavior of piezoelectrically layered perforated nanobeams. The obtained results demonstrate that incorporation of the nondimensional elastic foundation parameters, Kp = 2 and Kw = 20, results in a reduction in the relative percentage reduction in the maximum nondimensional mechanical transverse deflection due to increasing the perforation filling ratio from 0.2 to 1 from 199.86% to 91.83% for a point load and 89.39% for a uniformly distributed load. On the other hand, with Kp = 5 and Kw = 50, the relative percentage difference of the electromechanical bending deflection due to increasing the piezoelectric coefficient, e311, reaches about 8.7% for a point load and 8.5% for a uniformly distributed load at a beam aspect ratio of 50. Thus, the electromechanical as well as mechanical behaviors could be improved by controlling these parameters. The proposed methodology and the obtained results are supportive in many industrial and engineering applications, i.e., MEMS/NEMS.